Distinct impact of splenic denervation and the role of TRPV1 in LIPUS-induced anti-inflammatory milieu in the kidney: Involvement of neurochemicals, Nrf2/HO-1 modulation and change of macrophage phenotype - Omaima Mohammed Abdelwahed; Basma Emad Aboulhoda; Sarah Ali Abdelhameed Gouda; Tarek Shoukry; Laila Rashed; Marwa Alkaffas; Ebtehal Gamal Abdelhady; Mansour A. Alghamdi; Hend Abdalla; Nivin Sharawy (Tissue and Cell, 2026)

Participatory Co-Design for Human–Elephant Coexistence: Integrating Local Knowledge into Early Warning System Planning in Odisha - Balu M. Menon; Tarek Rashed; Lekshmi Venkitesh P; Vasundharan Nidhi; Rao R. Bhavani (Environmental Management, 2026)

Linking the blue economy to Women's empowerment to create avenues for the realization of ocean sustainability targets in the global south - Baker Matovu; Raimund Bleischwitz; Isaac Lukambagire; Linda A. Etta; Meltem Alkoyak-Yildiz; Rashed Tarek; Ming-An Lee; Mubarak Mammel; S. Anusree; Ammu S. Suresh (Ocean & Coastal Management, 2025)

Enhancing the nutritional values of egg yolks of laying hens by different dietary sources of omega-3 fatty acids, vitamin e and trace elements - Youssef Attia; Ahmed A.Al Sagan; El-Sayed O.S. Hussein; Marai J. Olal; Tarek A. Ebeid; Abdulaziz A. Alabdullatif; Rashed A. Alhotan; Mohammed M. Qaid; Vincenzo Tufarelli; Gianluca Pugliese; Khaild A. Asiry; Sameer A. Nagadi; et al. (Livestock Science, 2024)

Dietary flaxseed cake influences on performance, quality, and sensory attributes of eggs, serum, and egg trace minerals of laying hens - Youssef A. Attia; Ahmed A. Al-Sagan; El-Sayed O. S. Hussein; Marai J. Olal; Tarek A. Ebeid; Abdulaziz A. Al-Abdullatif; Rashed A. Alhotan; Salem R. Alyileili; Heba A. Shehata; Vincenzo Tufarelli (Tropical Animal Health and Production, 2024)

Infectious Pepper Mild Mottle Virus and Human Adenoviruses as Viral Indices in Sewage and Water Samples - Mohammed Kamal Rashed; Waled Morsy El-Senousy; ElSayed Tarek Abd ElSalam Sayed; Maha AlKhazindar (Food and Environmental Virology, 2022)
The objective of this study was to compare human adenoviruses (HAdVs) genome and infectivity, polyomaviruses (JC and BK) genome (JCPyVs) and (BKPyVs), Pepper Mild Mottle Virus (PMMoV) genome and infectivity, and infectious bacteriophages as viral indices for sewage and water samples. One hundred and forty-four samples were collected from inlets and outlets of water and wastewater treatment plants (WTPs), and WWTPs within Greater Cairo from October 2015 till March 2017. Two methods of viral concentration [Aluminium hydroxide (Al(OH) 3 ) precipitation method and adsorption-elution technique followed by organic flocculation method] were compared to determine which of them was the best method to concentrate viruses from sewage and water. Although samples with only one litre volume were concentrated using Al(OH) 3 precipitation method and the same samples with larger volumes (5–20 L) were concentrated using the adsorption-elution technique followed by the organic flocculation method, a non-significant difference was observed between the efficiency of the two methods in all types of samples except for the drinking water samples. Based on the qualitative prevalence of studied viruses in water and wastewater samples, the number of genome copies and infectious units in the same samples, resistance to treatment processes in water and wastewater treatment plants, higher frequency of both adenoviruses and PMMoV genomes as candidate viral indices in treated sewage and drinking water was observed. The problem of having a viral genome as indices of viral pollution is that it does not express the recent viral pollution because of the longer survivability of the viral genome than the infectious units in water and wastewater. Both infectious adenovirus and infectious phiX174 bacteriophage virus showed similar efficiencies as indices for viral pollution in drinking water and treated sewage samples. On the other hand, qualitative detection of infectious PMMoV failed to express efficiently the presence/absence of infectious enteric viruses in drinking water samples. Infectious adenoviruses and infectious bacteriophage phiX174 virus may be better candidates than adenoviruses genome, polyomaviruses genome, and PMMoV genome and infectivity as viral indices for water and wastewater.